A Detailed Study of the Relationships between Teaching, Support, Supervision and Role Modelling in Clinical Areas, within the Context of the Project 2000 Courses - White, Edward; English National Board for Nursing, Midwifery and Health Visiting, London ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1993)
A study examined the relationships between teaching, support, supervision, and role modeling in clinical areas in nursing education courses within the context of Britain's Project 2000, an educational reform initiative. The main data sources were semistructured interviews with a total of 53 students, 37 practitioners, and 15 tutors in 3 nurse education centers and case studies conducted in 3 adult branch centers and 3 mental health branch centers. It was widely reported that the helping roles adopted by practitioners and tutorial staff were often understood in different ways, not systematically assigned, and relegated according to competing demands. Most practitioners wanted greater clarification of their different roles, greater familiarity with the Project 2000 curriculum, and training in assessment. Students wanted longer placements and more contact with practitioners. Assessment of students' practice was deemed problematic. Tutorial staff played an insignificant role in assessing practice, and no intentional role modeling was reported. Learning objectives were not always regarded as realistic, and tutors complained that not all practitioners commanded the knowledge necessary for working with the students. Appendixes include the following: tables detailing respondents' responses and characteristics; study timetable; interview schedules/guides; fragment of verbatim transcript of one interview; and observation protocol. Contains 139 references.) (MN)
Availability: English National Board for Nursing, Midwifery and Health Visiting, Publications Dept., Victory House, 170 Tottenham Court Road, London, England W1P 0HA, United Kingdom (12.50 British pounds).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Case Studies; Clinical Teaching (Health Professions); Educational Change; Foreign Countries; Literature Reviews; National Surveys; Nurses; Nursing Education; Obstetrics; Postsecondary Education; Questionnaires; Role Models; Student Attitudes; Teacher Attitudes; Teacher Role; Teacher Student Relationship; United Kingdom; Reports, Research